O uso da metodologia TEAM-BASED LEARNING (TBL) aliada à tecnologia: percepções sobre a aprendizagem de contabilidade básica no Curso Técnico em Administração - GIACOMELLI, Sandra Cristina Pelegrini (2020)
The present dissertation, inserted in the Master Degree in Education of the University of the West Paulista, in the line of research Formation and Pedagogic Practice of the Teaching Professional, had as it’s main goal evaluate the contributions of the usage of the active learning methodology TEAM-BASED LEARNING (TBL), allied to the app TBL Active, to the learning of basic concepts of Accountancy in the Administration Technical Course. The theoretic base to discuss the TBL methodology supported it-self in the authors Berbel, Bollela, Krug et al and Michaelsen; to discuss the experiential learning , the backing was on the authors Krakauer, Pepler, Peterson and Pimentel; and the foundation of the active methodology and technological were guided in the authors Coll and Monereo, Dewey, Moran and Valente. The quality and quantity research, of the intervention kind, was executed in a class with 40 students of the subject accounting operational process of the Technical Administration Course, in a public school in a small size city, in the inland of São Paulo. The gather of data involved the observation during the whole intervention process; beyond the interview with the teacher and the questionnaire with the students. The diagnosis interview with the teacher aimed identify the methods used by the teacher in the teaching process; the interview at the end of the of the intervention aimed evaluating the teacher’s perception regarded to the methodology applied and the results reached. To the students were applied questionnaires with different goals, being the first to verify the profile of each one of the students. During the intervention, to obtain pertinent data of the learning construction progress, the same questionnaire had two different applications: the individual, at the beginning of the activity, to verify each student learning about the content worked, and the other one is to the discussion of the same questionnaire giving the answers by consensus of the team formed; being all the answers analyzed by the documents generated by the TBL Active. At the end of the intervention were applied, online, one questionnaire to verify the perception of the individual learning and the team learning; and another one to analyze the experience of the students in the learning process of the concepts within the accounting topic, with the usage of the TBL. All the data collected were analyzed from the following categories: the practical accounting learning; the collaborative team learning; and the TBL validation. The results evidenced that occurred a practical learning of the accounting and there was a crescent rate of hits by comparing the individual answers and the team ones. The professor reported that the applied intervention reached superior results over other methods. From the students, 81,5% totally agreed that the team work provided collaborative learning and 85,2%agreed that the use of technology in the classroom provided easiness and practicality to the classes. The TBL was validated by students and teacher who highlighted that intend to use it again and stressed that the methodology provided the active participation and the significant learning of the content.